STUDY OF MESH DEPENDENCY ON NUMERICAL MODELING FOR SLOPE STABILITY ANALYSIS BASED ON MOHR-COULUMB CRITERIA - Aliy Arrasyd Gustam, Muh.
The mining sector is an industrial sector with a high level of work accident risk in every activity, therefore a risk control is needed in anticipating accidents that may occur. One of the risk controls from mining activities is to design a stable mine slope. In this study, the slope was modeled using the limit equilibrium method and finite element method in Slide2 and RS2 software with Mohr-Coulumb criteria as input parameters. The modeling is done by varying the shape of the elements and number of nodes around the external boundary of slope of 50 to 500 with multiples of 50 with the rock having strain softening and perfect elastoplastic behavior. Factor of safety on the slope depends on the number of points around the slope. Variations between the geometric shape of the mesh and the number of nodes affect the factor of safety, where the relationship is that as more points increase, factor of safety also decreases. However, factor of safety tends to be constant when using a large number of nodes, in this case 250 or more. In calculating factor of safety on slope using limit equilibrium method, the result is greater than finite element method. In the calculation on factor of safety on slope using limit equilibrium method, factor of safety is 1.873, while on finite element method, factor of safety is on the range of 1.27-1.68 for rock with strain softening behavior and 1.73-2.28 for rock with perfect elastoplastic behavior.